Mixed Epithelial and Stromal Tumor: A Rare Renal Neoplasm—Case Report with Clinicopathologic Features and Review of the Literature - Mukund Tinguria; Katherine Chorneyko (Case Reports in Pathology)
Mixed epithelial and stromal tumor (MEST) is a rare benign renal neoplasm composed of epithelial and stromal components. Here, we report a 61-year-old woman presenting with a left complex cystic renal mass. The lesion was found incidentally on ultrasound for abdominal discomfort. CT scan and MRI showed a 7.4 cm complex cystic lesion in the left kidney. The differential diagnoses included complex renal cyst and cystic renal cell carcinoma. Laparoscopic nephrectomy showed a large 7.5 cm multicystic tumor with thick and thin septae and smooth walled-cysts containing clear watery fluid. Histologic examination showed variable sized cysts lined by flattened, cuboidal to columnar epithelium with focal hobnailing. No significant cytologic atypia or mitoses were noted. The cyst lining epithelium was positive for CK7 and high molecular weight cytokeratin (34Be12). The stroma was positive for alpha smooth muscle actin, CD10, estrogen receptor, and progesterone receptor. This report contributes an additional case to our collective knowledge of these lesions and summarizes the literature around these rare neoplasms.